The Effectiveness of Entrepreneurship Week Activities to Increase The Creativity of Entrepreneurial Students at PGRI Palembang University - Muhammad Toyib; Zahruddin Hodsay; Diana Widhi Rachmawati (research, training and philanthropy institution Natural Aceh, 2023)
The goal is to find out the effectiveness of entrepreneurship week activities in increasing the creativity of entrepreneurial students. The research methodology used is descriptive quantitative. As for data collection techniques, documentation and questionnaires, 35 statements are used that have been tested for validity and reliability first. Where the greater the percentage achieved, the higher the effectiveness of activities in increasing student creativity in entrepreneurship. The results showed that of the 6 indicators tested, it showed that the 1st indicator was 78.13%, the 2nd indicator was 70.71%, the 3rd and 4th indicators were 84.43, the 5th indicator was 85.57 and the 6th indicator was 90%. Based on the results of the study, it can be concluded that the effectiveness of entrepreneurship week activities to increase the creativity of entrepreneurial students averages 82.38 percent in the high category. While the most chosen type of business is the culinary field as much as 97.7% and the remaining 2.3% are handicrafts.